2019
DOI: 10.1088/1757-899x/518/3/032035
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of flat plate solar collector performance with twisted heat pipe

Abstract: In this work, a system of heat pipe is implemented to improve the performance of flat plate solar collector. The experiment rig consists of sun light simulator, flat plate, heat pipe (wickless), heat exchanger, and measurement instruments. The model is represented by twisting portion of the evaporator section and also inclined by an angle of 30° with a constant total length of 1140 mm. In this model the evaporator, adiabatic and condenser lengths are 780mm, 140mm and 230mm respectively. The omitted energies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As shown in figure (6), temperature gradient vs. heat duty for various sink temperature. The temperature difference has unordinary behavior for various sink temperature.…”
Section: Effect Of Heat Duty Input On Temperature Gradientmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in figure (6), temperature gradient vs. heat duty for various sink temperature. The temperature difference has unordinary behavior for various sink temperature.…”
Section: Effect Of Heat Duty Input On Temperature Gradientmentioning
confidence: 99%
“…The results also indicated the gradient between mean temperature of condenser and evaporator was rises likewise the energy transferred increases. Basil N, et.al (2019) [6] studied the flat plate type solar heater with thermosyphon experimentally. The experimental system consists of solar irradiation simulator, flat plate solar collector heater, heat pipe (wickless), heat exchanger equipment and measurement devices.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (5) shows the temperature distribution along the axial direction of the thermosyphon tube for the filling ratio of 13.6%, condenser cooling water flow rate 16 LPM, and different area ratio. It can be observed that the temperature slight decrease up to x =1.5 m from the evaporator base and then decreases along the condenser section.…”
Section: Temperature Distribution Along the Thermosyphonmentioning
confidence: 99%
“…Merzha et al, [5] enhanced the performance of flat plate solar collector using the heat pipe. The experimental test is represented by twisting portion of the evaporator section and also inclined by an angle of 30° with a constant total length of 114 cm.…”
Section: Introduction and Literature Reviewsmentioning
confidence: 99%